(untitled) (Baghdad Science Journal, 2008)
120 samples were collected from children (ages between new born and 10 years) who infected with oral thrush. The results revealed that the Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (MFC) of extracted oil of lemon grass against C.albicans, C.tropicalis, C.keyfr, C.glabrata and C.guilliermondii were 1.25,1.25,1.25,2.5 and 2.5µl/ml and 2.5, 2.5, 2.5, 5 and 5 µl /ml respectively. while the (MIC) and (MFC) for the extraction oil of thyme against C.albicans, C.tropicalis, C.keyfr, C.glabrata and C.guilliermondii were 0.6, 0.6, 1.25, 1.25, and 1.25µl/ml and 1.25, 1.25, 2.5, 2.5, and 2.5µl/ml respectively . While the value of (MIC) and (MFC) for Nystatin against Candida species were 32 and 64 µg / ml respectively. On the other hand the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) value of exctracted oil for lemon grass against E.coli, S. aureus and S. pyogenes were 5, 2.5 and 2.5 µl/ml and 10 , 5 and 5µl /ml respectively. while the (MIC) and (MBC) value of exctracted oil for thyme against E.coli, S. aureus and S. pyogenes were 2.5, 2.5 and 1.25 µl/ml and 5 , 5 and 2.5µl /ml respectively.